2022
DOI: 10.1186/s41927-022-00279-7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of work and social participation in patients with psoriatic arthritis in the Netherlands: an observational study

Abstract: Background Psoriatic arthritis can cause pain, disability, and permanent joint damage. This can lead to impairments in work and social participation. Little is known about the extent of these impairments in routine practice. With this study, we aim to examine the extent of work and activity impairment in (subgroups of) Dutch patients with psoriatic arthritis (PsA), and to examine determinants associated with this impairment. Methods This is an obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Results from our study indicate that female genital LS exerts a negative impact on work productivity. Similar conclusions were drawn in other research on different chronic diseases: psoriasis, psoriatic arthritis and rheumatoid arthritis [ 21 23 ]. Moreover, Villacorta outlined that psoriasis influences economic burden and is also connected with indirect costs caused e.g.…”
Section: Discussionsupporting
confidence: 90%
“…Results from our study indicate that female genital LS exerts a negative impact on work productivity. Similar conclusions were drawn in other research on different chronic diseases: psoriasis, psoriatic arthritis and rheumatoid arthritis [ 21 23 ]. Moreover, Villacorta outlined that psoriasis influences economic burden and is also connected with indirect costs caused e.g.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have demonstrated associations between productivity and response (minimal disease activity [MDA] or low disease activity according to PsA Disease Activity Score [PASDAS]) [ 10 , 40 ] and found greater improvements in productivity with bDMARDs than with csDMARDs [ 41 ]. Generally, the estimated effects of the b/tsDMARDs in the current analysis were similar with respect to improving a patient’s capacity to work and participate in leisure activities.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, patients with PsA have reported its effect on individual activities and social participation, as well as physiological functioning as linked to the World Health Organization (WHO) International Classification of Functioning, Disability, and Health (ICF) [ 4 , 5 ]. The consequences of PsA on work are important and include deleterious effects such as hours of missed work (absenteeism), diminished productivity while at work (presenteeism), and increased economic burden due to indirect costs [ 4 , 6 10 ].…”
Section: Introductionmentioning
confidence: 99%